Uma proposta de sequência didática em website para o ensino de transferência de calor - Oliveira, Emanuel Romário (2018)
The pedagogical practice is constantly changing. The contents are updated, the way of learning evolves, and students reach school age with more information than before the digital age. Teaching in this context requires a dynamic, versatile and up-to-date teacher. One of the challenges is the training of teachers who teach Physics, since many have no degree in the field. Furthermore, teachers have insufficient time to prepare more engaging and thought-provoking lessons. After having analyzed this panorama, the didactic sequence of teaching about heat transfer has been proposed. It presents an investigative teaching format in which the teacher instigates the students with questions meant to cause a cognitive conflict. The questions are answered initially with the prior knowledge of the students. Afterwards, teachers and students seek solutions to the presented problems, that is done through experiments and discussions. After answering the initial questions, the conclusions obtained are extended to other cases. The didactic sequence is presented in a website format. There are resources for teachers and students to use such as simulators, animated figures, application image gallery, motivational videos and experiment videos. It has been observed in the classes that the students were motivated to learn concepts of Physics. It is expected that teachers, using this methodology, also feel that their goal as facilitators of knowledge construction is being achieved.